A review of workability of wrought magnesium alloys - Harun, Mohd. Ruzi; Muhamad, Norhamidi; S., Abu Bakar; Jamaludin, Khairur Rijal; M. N., Nor Hafiez; Ahmad, Sufizar; Ibrahim, Mohd. Halim I.; Murtadhahadi, Murtadhahadi (2009)
Despite being the lightest structural metal, magnesium alloys exhibited poor workability at low temperatures due to their hexagonal closed-packed crystal structure, consequently required them to be processed at elevated temperature. Their highly affinity to oxygen lead them to an easy oxidation. Moreover, they are poor corrosion resistance, poor creep resistance as well as fatigue failure but these can be improved by various techniques of surface treatments and alloying additions. Commercial wrought magnesium alloy grades, its mechanical properties as well as its workability at elevated temperatures are presented. Recent literatures showed that the workability of these alloys is increased at temperatures ranging from 100 to 3500C, 200 to 400 to 300 to 5000C and for AZ, ZK and WE alloy systems, respectively. The purpose of this paper is to review and reveal the issues in processing of wrought magnesium alloys